2005
DOI: 10.1016/j.cell.2004.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Sterile 20 Kinase Phosphorylates Histone H2B at Serine 10 during Hydrogen Peroxide-Induced Apoptosis in S. cerevisiae

Abstract: Apoptosis is a highly coordinated cell suicide mechanism in vertebrates. Phosphorylation of serine 14 of histone H2B, catalyzed by Mst1 kinase, has been linked to chromatin compaction during apoptosis. We extend these results to unicellular eukaryotes by demonstrating that H2B is specifically phosphorylated at serine 10 (S10) in a hydrogen peroxide-induced cell death pathway in S. cerevisiae. H2B S10A mutants are resistant to cell death elicited by H(2)O(2) while H2B S10E phospho-site mimics promote cell death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
195
1
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(213 citation statements)
references
References 36 publications
10
195
1
1
Order By: Relevance
“…For Ste20, nuclear translocation has been proposed to allow it to phosphorylate histone H2B and promote apoptosis in response to oxidative stress (Ahn et al, 2005), but preliminary tests suggest that neither the BR domain nor the CRIB domain is required for this process (S.-H. Ahn and C. D. Allis, personal communication). Gic1 shows some nuclear affinity, but chimeras that lack this localization still function normally (see Figure 7D).…”
Section: Roles For Charge and Hydrophobicitymentioning
confidence: 99%
“…For Ste20, nuclear translocation has been proposed to allow it to phosphorylate histone H2B and promote apoptosis in response to oxidative stress (Ahn et al, 2005), but preliminary tests suggest that neither the BR domain nor the CRIB domain is required for this process (S.-H. Ahn and C. D. Allis, personal communication). Gic1 shows some nuclear affinity, but chimeras that lack this localization still function normally (see Figure 7D).…”
Section: Roles For Charge and Hydrophobicitymentioning
confidence: 99%
“…H2A and H2B have been reported to possess acetylation (H2A: K5, K9 and H2B: K5, K12, K15, K20), phosphorylation (H2A: S1 and H2B: S10), monomethylation (H2A: K15 and H2B: K5, K43) and ubiquitination (H2A: K119 and H2B: K120/K123) [1,14,16,[36][37][38][39][40]. Thus the unambiguous assignment of the species in these profiles is complicated by possible presence of these modifications along with the variants.…”
Section: Core Histone Profilesmentioning
confidence: 99%
“…Lehtinen et al (2006) reported that MST1 is activated by H 2 O 2 and induces cell death by phosphorylating the transcription factor FOXO in primary mammalian neurons. Furthermore, Ste20 mediates H 2 O 2 -induced cell death by phosphorylating histone H2B in Saccharomyces cerevisiae (Ahn et al, 2005). These studies implicate MST1 as a crucial kinase in H 2 O 2 -induced cell death, but MST1 activation mechanisms by H 2 O 2 have yet to be clarified.…”
Section: Introductionmentioning
confidence: 99%